Crustacean fishery with bottom traps in an area of the southern Tyrrhenian Sea: species composition, abundance and biomass - CASTRIOTA, L.; FALAUTANO, M.; ROMEO, T.; FLORIO, J.; PELUSI, P.; FINOIA, M.G.; ANDALORO, F. (Mediterranean Marine Science, 2004)
The north-eastern coast of Sicily is characterized by deep, steep bottoms, not easily exploitable by trawl fishery. In this area few fishermen use bottom traps to catch shrimps and Norway lobsters. Our studies were aimed at identifying the species’ composition, abundance and biomass of crustaceans exploitable by bottom traps in this area. Monthly samples over one year were obtained from two lines of 30 baited traps each, at depths between 100 and 500 m. One line was placed in an area usually exploited by this fishery; the other line was used in the unexploited deepest bottoms. Trapped specimens were counted and weighed. ANOVA test, post hoc multiple comparisons and Student’s t test were applied on abundance and biomass data, for testing differences between areas, among seasons and species. During 22 fishing days, 23 species characteristic of the bathyal mud assemblage were caught, 8 of which were not considered commercial. Plesionika edwardsii was the most important species, recorded in the whole bathymetric range investigated; Nephrops norvegicus was significantly higher in terms of biomass in the unexploited area. The discard, of slight importance, was mostly represented by the crab Liocarcinus depurator. Spring season yielded the best catches in both areas, showing the highest values for both abundance and biomass